Faktor Dukungan Keluarga terhadap Kualitas Hidup Penderita Systemic Lupus Erithematosus (SLE) - Lilis Silaban; Yulastri Arif; Reni Prima Gusti (Journal of Telenursing (JOTING), 2023)
This study aims to analyze the factors of family support that affect the quality of life of SLE sufferers. The method used is descriptive analytics with a cross-sectional approach. The results showed that family support for SLE sufferers was relatively good (57.8%); family support factors and emotional, instrumental, informational and appreciation support sub-variables that are related to the quality of life based on functional domains obtain a mean sample value of -0.068, social support = -0.0687, physical health = -0.068 and psychological = -0.068, the significant direction of the positive relationship (11.407), social support (10.865), physical health (11.015) and psychological (10.680) > 1.96. In conclusion, there is a significant relationship between family support and quality of life in SLE sufferers' functional and social support domain and physical and psychological health. Keywords: Family Support, Quality of Life, Systemic Lupus Erythematosus